Under the stars [videorecording (DVD)] - Vinuesa, Victoria; Pettyfer, Alex, 1990-; De Dominici, Eva; Riotta, Vincent; Serfaty, Jessica; Iezzi, Chiara; Estes, Rob, 1963-; Collette, Toni; Garcia, Andy; Guerra, Andrea, 1961-; Ferrantini, Chiara; Malavasi, Pierluigi Gigi (Decal, 2025)
"Under the Stars follows a struggling romance novelist trapped in a lifeless relationship and plagued by writer's block. Hoping to reignite his passion, he travels to Italy for inspiration--only to unexpectedly fall for a spirited local who challenges everything he thought he knew about love and himself."--